2015
DOI: 10.1039/c5ra14224e
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model and experimental validation of the local damage mechanism of solid lubricant films for metal matrix self-lubricating composites

Abstract: To explore the local damage mechanism of solid lubricant film for metal matrix self-lubricating composites, a simplified model for analyzing sliding friction contact and a mathematical model for calculating surface stresses of solid lubricant film are built. Based on the analytical model, we investigate the local damage mechanisms of solid lubricant films under different experimental conditions in theory. Theoretical analyses suggest that surface damages can still occur in the local regions of solid lubricant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[8][9][10] Tribology researchers such as Xu et al 10 and Yang et al 11 probed the friction and wear behavior of TiAl-10 wt% Ag (TA) sliding against xed Si 3 N 4 ball and found that silver was gradually squeezed out of TA with the structure evolution of the friction layer and enriched the wear scar, which caused TA to obtain the small friction coefficient and less wear rate. Xu et al 12 studied the anti-friction and anti-wear property of silver lubricating lm, and found that silver lubricating lm exhibited low friction and less wear for the plastic deformation of silver. In addition, it was also found that silver lubricating lm possessing low tensile strength of about 140-170 MPa was easily destroyed by the high von Mises contact stress, 13 which was not advantageous towards the improvement of the antifriction and anti-wear properties.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Tribology researchers such as Xu et al 10 and Yang et al 11 probed the friction and wear behavior of TiAl-10 wt% Ag (TA) sliding against xed Si 3 N 4 ball and found that silver was gradually squeezed out of TA with the structure evolution of the friction layer and enriched the wear scar, which caused TA to obtain the small friction coefficient and less wear rate. Xu et al 12 studied the anti-friction and anti-wear property of silver lubricating lm, and found that silver lubricating lm exhibited low friction and less wear for the plastic deformation of silver. In addition, it was also found that silver lubricating lm possessing low tensile strength of about 140-170 MPa was easily destroyed by the high von Mises contact stress, 13 which was not advantageous towards the improvement of the antifriction and anti-wear properties.…”
Section: Introductionmentioning
confidence: 99%
“…An resultful method of optimizing the friction and wear behavior of TiAl alloy is to fabricate TiAl based self‐lubricating composites by adding solid lubricants . Silver, for the low shearing resistance, excellent plastic deformation, and high plastic ductility, could be preferentially selected to provide the low friction and less wear of TiAl alloys . Shi et al and Xu et al utilized spark plasma sintering to prepare TiAl based composite containing 10 wt%Ag (TiAl–10 wt%Ag), and found that the excellent tribological property of TiAl–10 wt%Ag was obtained at 450 °C, if compared to those at other temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Silver, for the low shearing resistance, excellent plastic deformation, and high plastic ductility, could be preferentially selected to provide the low friction and less wear of TiAl alloys . Shi et al and Xu et al utilized spark plasma sintering to prepare TiAl based composite containing 10 wt%Ag (TiAl–10 wt%Ag), and found that the excellent tribological property of TiAl–10 wt%Ag was obtained at 450 °C, if compared to those at other temperatures. Tronci et al and Arash et al studied the anti‐friction and anti‐wear performance of silver coating, and found that the excellent friction and wear property of silver coating was mainly attributed to the low shearing resistance, outstanding plastic deformation, and high plastic ductility of silver.…”
Section: Introductionmentioning
confidence: 99%